Ivermectin for the prevention of COVID-19: addressing potential bias and medical fraud. (22nd February 2022) - Hill, Andrew; Mirchandani, Manya; Ellis, Leah; Pilkington, Victoria
Abstract: Background: Ivermectin is an antiparasitic drug being investigated in clinical trials for the prevention of COVID-19. However, there are concerns about the quality of some of these trials. Objectives: To conduct a meta-analysis with randomized controlled trials of ivermectin for the prevention of COVID-19, while controlling for the quality of data. The primary outcome was RT–PCR-confirmed COVID-19 infection. The secondary outcome was rate of symptomatic COVID-19 infection. Methods: We conducted a subgroup analysis based on the quality of randomized controlled trials evaluating ivermectin for the prevention of COVID-19. Quality was assessed using the Cochrane risk of bias measures (RoB 2) and additional checks on raw data, where possible. Results: Four studies were included in the meta-analysis. One was rated as being potentially fraudulent, two as having a high risk of bias and one as having some concerns for bias. Ivermectin did not have a significant effect on preventing RT–PCR-confirmed COVID-19 infection. Ivermectin had a significant effect on preventing symptomatic COVID-19 infection in one trial with some concerns of bias, but this result was based on post hoc analysis of a multi-arm study. Conclusions: In this meta-analysis, the use of ivermectin was not associated with the prevention of RT–PCR-confirmed or symptomatic COVID-19. The currently available randomized trials evaluating ivermectin for the prevention of COVID-19 are insufficient and of poor quality.